Comment on ‘Coupled anharmonic oscillators: the Raileigh–Ritz approach versus the collocation approach’ - Amore, Paolo (2011)
We show that some of the conclusions drawn recently about the performance and convergence of the little sinc functions collocation method are misleading. To this end, we prove the convergence of the method and recalculate the ground-state energy for the Pullen–Edmonds Hamiltonian. In addition, we show the results for another nonseparable Hamiltonian operator with a somewhat more complicated potential-energy function.